Efficacy of ormeloxifene versus oral contraceptive in the management of abnormal uterine bleeding due to uterine leiomyoma. Issue 12 (20th September 2016) - Kriplani, Alka; Srivastava, Astha; Kulshrestha, Vidushi; Kachhawa, Garima; Agarwal, Nutan; Bhatla, Neerja; Hari, Smriti
Abstract: Aim: To compare ormeloxifene with combined oral contraceptive (COC) in abnormal uterine bleeding (AUB) due to leiomyoma (AUB‐L). Methods: Fifty women with AUB‐L were randomized after informed consent and institute ethics clearance. Group I (n = 25) was given ormeloxifene (a SERM i.e. selective estrogen receptor modulator) 60 mg twice per week and group II (n = 25) was given COC (ethinyl estradiol 30 μg with desogestrel 150 μg) on days 1–21 for 6 months. Menstrual blood loss was assessed on pictorial blood loss assessment chart (PBAC) score and leiomyoma volume was assessed on ultrasound. Fibroids were classified according to FIGO‐PALM‐COEIN classification for AUB where leiomyomas were further sub‐classified as types 0 to 8 according to their location. Follow up was done at 1, 3, 6 and 9 months. Results: Mean PBAC score reduced by 81% with ormeloxifene (group I) compared with 43.8% for COC (group II). After 6 months, 18 patients (72%) in group I had PBAC score in the non‐menorrhagic range (<100) compared with only two (8%) in group II. In group I, PBAC score in FIGO‐PALM‐COEIN leiomyoma types 2, 3, 4, 5, 6 reduced by 90.2%, 82.5%, 93.3%, 56.4% and 100%, respectively and 14 (56%) developed amenorrhea; compared with reduction of 64%, 27.5%, 25.9% in types 4, 5 and 6, respectively in group II. Dysmenorrhea visual analog scale score decreased in both groups. Mean leiomyoma volume increased in both groups: by 25.7% with ormeloxifene versus 16.9% with COC; only grade 2 leiomyoma in group I reduced by 44%. One patient in group II with grade 2 leiomyoma discontinued treatment at 3 months. Seven patients (28%) developed ovarian cyst in group I with no other major adverse effect in either group. Conclusion: Ormeloxifene with its convenient twice‐weekly dosage schedule was effective in treating AUB‐L, with 72% of patients responding to 6‐month treatment compared with 8% with COC, even though leiomyoma volume increased insignificantly with both ormeloxifene and COCs.